2020
DOI: 10.4330/wjc.v12.i6.248
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance in myocardial infarction with non-obstructive coronary arteries patients: A review

Abstract: The diagnosis of myocardial infarction with non-obstructive coronary arteries (MINOCA) necessitates documentation of an acute myocardial infarction (AMI), non-obstructive coronary arteries, using invasive coronary angiography or coronary computed tomography angiography and no clinically overt cause for AMI. Historically patients with MINOCA represent a clinical dilemma with subsequent uncertain clinical management. Differential diagnosis is crucial to choose the best therapeutic option for ischemic and non-isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 68 publications
0
14
0
2
Order By: Relevance
“…Differential diagnoses of MINOCA include plaque erosion or rupture with spontaneous recanalization, coronary embolism, spontaneous coronary artery dissection, microvascular disease, stress cardiomyopathy, and myocarditis. Due to the broad differential diagnosis of MINOCA, treatment and prognosis vary remarkably [ 3 , 4 ]. CMR is a powerful tool in assessing patients with MI due to its ability to diagnose acute and chronic MI, narrow the differential diagnosis, and determine the prognosis by assessing the scar burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential diagnoses of MINOCA include plaque erosion or rupture with spontaneous recanalization, coronary embolism, spontaneous coronary artery dissection, microvascular disease, stress cardiomyopathy, and myocarditis. Due to the broad differential diagnosis of MINOCA, treatment and prognosis vary remarkably [ 3 , 4 ]. CMR is a powerful tool in assessing patients with MI due to its ability to diagnose acute and chronic MI, narrow the differential diagnosis, and determine the prognosis by assessing the scar burden.…”
Section: Discussionmentioning
confidence: 99%
“…CMR is a powerful tool in assessing patients with MI due to its ability to diagnose acute and chronic MI, narrow the differential diagnosis, and determine the prognosis by assessing the scar burden. In patients with MINOCA, CMR should be obtained within seven days of presentation and preferably not in the first 24 hours to improve the diagnostic accuracy [ 3 ]. CMR protocol should include cine assessment of cardiac function and structure, T2 assessment of myocardial edema, and LGE to assess for macroscopic scar/fibrosis/infiltrative disease (both pattern and extent) [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…A mild form of acute myocarditis can determine non-specific symptoms that don't lead the subject to require medical assistance. Another important reason is the under-use of Cardiovascular Magnetic Resonance in myocardial infarction with non-obstructive coronary arteries (MINOCA) patients [21] . The under-reporting phenomena, well known and well described in literature 22 , 23 , can contribute to the underestimation of this adverse event in the post-marketing surveillance phase.…”
Section: Discussionmentioning
confidence: 99%
“…This was also reiterated by the European Society of Cardiology (ESC) [ 1 , 54 ]. CMR can help establish the diagnosis of MINOCA by ruling out conditions with similar presentations, including stress-induced, hypertrophic, or dilated cardiomyopathies, myocarditis, and MI-CAD [ 55 ]. It has been suggested that CMR can identify the underlying etiology in nearly two thirds of MINOCA cases, as well as provide prognostic and stratification data that can change therapeutic strategies in as many as half of cases [ 56 , 57 ].…”
Section: Minoca Work-up and Clinical Treatment Regimensmentioning
confidence: 99%